Purificação, caracterização bioquímica e atividade biológica in vitro contra insetos praga de um novo inibidor de tripsina isolado de sementes de Sapindus saponaria L. (Sapindaceae) - Lima, Glauber Pacelli Gomes de (2012)
Environmental toxicity, low biodegradability and increased resistance in agricultural pest insects and in insect vectors of diseases to insecticides traditionally used for their control have encouraged the development of chemical alternatives with greater specificity and biodegradability especially from plants. In this way, the present study aimed the purification, characterization and evaluation of activity towards pest insect digestive enzymes of a new trypsin inhibitor obtained from Sapindus saponaria seeds. This new trypsin inhibitor obtained from S. saponaria seeds (SSTI2) belongs to Potato I inhibitor family and was purified by protein precipitation with trichloroacetic acid, affinity chromatography and reverse phase chromatography using UFLC system. The native inhibitor and its fragments generated by enzymatic treatment with trypsin and pepsin were analyzed and sequenced by MALDI-TOF and ESI-TOF mass spectrometry, determining its accurate molecular mass (MM = 7571, 976 Da) and primary structure (64 of 69 amino acids). The SSTI2 showed an IC50 of 8.3 x 10-2 μmol.L-1 against bovine trypsin, and a much lower inhibitory activity on the enzymes chymotrypsin (13.24 ± 0.28%) and papain (5.28 ± 0 , 42%), but was unable to inhibit proteolysis promoted by bromelain. In spite to show moderate inhibition of total digestive enzymes (4.74 ± 0.45% to 56.06 ± 1.41%), the inhibitor was very effective upon trypsin-like enzymes present in Aedes aegypti (92.44 ± 0.99%), Anthonomus grandis (77.93 ± 0.12%), Anticarsia gemmatalis ( 32.21 ± 0.57%) and Spodoptera frugiperda (71.44 ± 1.23%) guts. This strong inhibitory effect of SSTI2 on the catalytic activity of trypsin-like peptidases of insect’s midguts suggests a possible suppressive effect on development and survival of insects fed with diets containing the inhibitor. Thus, future in vivo assays and evaluation of other biochemical properties will be important to establish the potential biotechnological application of SSTI2, especially for the combat of Ae. aegypti, A. grandis and An. gemmatalis. Furthermore, the sequence of SSTI2 elucidated in this study allows the chemical synthesis, cloning of coding gene sequence and heterologous expression of this potential new biotechnological tool.